2019
DOI: 10.1088/1361-6560/ab1d8a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a non-contact imaging scintillator-based dosimetry system for total skin electron therapy

Abstract: Surface dosimetry is required for ensuring effective administration of total skin electron therapy (TSET); however, its use is often reduced due to the time consuming and complex nature of acquisition. A new surface dose imaging technique was characterized in this study and found to provide accurate, rapid and remote measurement of surface doses without the need for post-exposure processing. Disc-shaped plastic scintillators (1 mm thick  ×  15 mm ) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Furthermore, the intensified camera used during this study has maximum detection efficiency in the wavelength band of EJ‐200 scintillator emission (400–500 nm) thereby suppressing and enhancing detection of Cherenkov and scintillation signal, respectively. Previous studies have demonstrated the feasibility of conducting surface dosimetry, treatment QA, and radiation field verification by capturing light emission from plastic scintillator targets during linear accelerator (linac)‐based radiotherapy . Thus, the optical imaging methods described in this study could also be adapted for use in linac TBI QA testing.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Furthermore, the intensified camera used during this study has maximum detection efficiency in the wavelength band of EJ‐200 scintillator emission (400–500 nm) thereby suppressing and enhancing detection of Cherenkov and scintillation signal, respectively. Previous studies have demonstrated the feasibility of conducting surface dosimetry, treatment QA, and radiation field verification by capturing light emission from plastic scintillator targets during linear accelerator (linac)‐based radiotherapy . Thus, the optical imaging methods described in this study could also be adapted for use in linac TBI QA testing.…”
Section: Resultsmentioning
confidence: 98%
“…In turn, workflow time can be minimized and there exists the possibility for reducing human error by automating data processing and analysis. There also exists the possibility of utilizing this system for patient imaging by incorporation of a modified version of a previously described equalized background subtraction method …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations